A economia política da dominância financeira: acumulação de capital e rentismo no capitalismo contemporâneo - Silva, Edson Mendonça da (2016)
In search of an understanding of the financialization process in major developed economies, the paper presents and explores the main interpretations of the phenomenon in political economy. For this, the paper analyzes the reference studies the issue, especially the Marxist, post-Keynesian and regulationist approaches, which offer a broad panorama of the debate and the main themes. And in order to analyze each contribution to the debate, work will focus on the effects of financialization on the process of capital accumulation and the accentuation of profiteering as striking feature of contemporary capitalism